Komunikasi Perempuan di Pondok Pesantren Salaf Al-Anwar Sarang Rembang Jawa Tengah - Moefad, Agoes Moh.; Naqqiyah, Maulidatus Syahrotin (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2019)
This article discusses the communication process of women and also their role in the Salaf Islamic boarding school environment. Women are part of the phenomenon of the boarding school community. In their daily lives, they are inseparable with various kinds of processes and the role of communication that goes through. In their daily life, women in the Salaf Islamic boarding school are classified as creatures whose scope of work is only in the domestic sector. Through an ethnographic approach, researchers conducted involved observations and also in-depth interviews with 6 informants chosen purposively. This study explains that the process of communication of women in Islamic boarding schools occurs persuasively, face-to-face and their role as housewives, teachers, and as children in the environment of the Salaf boarding school with a very limited scope.